2019
DOI: 10.1152/japplphysiol.00119.2019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral oxygen saturation and cerebral blood flow velocity under mild +Gz hypergravity

Abstract: We previously reported that cerebral blood flow (CBF) was reduced by even mild +Gz hypergravity. Regional cerebral oxygen saturation as measured by near-infrared spectroscopy (C-rSO2) has been widely used to detect cerebral ischemia in clinical practice. For example, decreases in C-rSO2 reflect reduced CBF or arterial oxygen saturation. Thus it was hypothesized that C-rSO2 would decrease in association with reduced CBF during mild hypergravity. To test this hypothesis, we measured CBF velocity by transcranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, virtual changes in rSO 2 as a result of changes in cerebral blood flow can be affected by hemoglobin concentration, FiO 2 , MAP, position, cerebral metabolic rate, oxygen dissociation curve, and ratio of cerebral arterial to venous blood volume, which can fluctuate during surgery. A previous study showed that cerebral oxygenation may not precisely reflect a decrease in cerebral blood flow during mild hypergravity [ 13 ]. Although NIRS does not directly measure cerebral blood flow, many studies have addressed the positive correlation between rSO 2 and PetCO 2 [ 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, virtual changes in rSO 2 as a result of changes in cerebral blood flow can be affected by hemoglobin concentration, FiO 2 , MAP, position, cerebral metabolic rate, oxygen dissociation curve, and ratio of cerebral arterial to venous blood volume, which can fluctuate during surgery. A previous study showed that cerebral oxygenation may not precisely reflect a decrease in cerebral blood flow during mild hypergravity [ 13 ]. Although NIRS does not directly measure cerebral blood flow, many studies have addressed the positive correlation between rSO 2 and PetCO 2 [ 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Practically, our results emphasized that HR acceleration induced by the activation of the baroreflex also plays a crucial role in G tolerance during the rapid onset profile. We would like to compare our findings with the results of different markers that directly reflect cerebral perfusion under G stress [33][34][35]. However, good physical fitness has been shown to increase pilots' AGSM efficiency and prolong the tolerated duration of simulated acrobatic combat maneuvers in the centrifuge [36].…”
Section: Discussionmentioning
confidence: 99%
“…Near-infrared spectroscopy (NIRS) is another method that has been suggested to be capable of measuring brain activityrelated physiological changes via noninvasive monitoring of oxygenation and deoxygenation of tissues underneath the sensor (Madsen and Secher, 1999). While reduced brain oxygenation due to decreased cerebral perfusion is expected to occur under hypergravity (Pollock et al, 2021), prolonged G-exposure effects on prefrontal cortex (PFC) oxygenation have been inconsistent in past reports (Kobayashi and Miyamoto, 2000;Kobayashi et al, 2002;Smith et al, 2013;Konishi et al, 2019). Due to historical sensing limitations, there is limited knowledge about the deoxygenation kinetics responses of the brain during repeated, acute G-exposure, especially high G-exposure (> 5G).…”
Section: Introductionmentioning
confidence: 99%